Nursing experience of partial thrombotic blockage of peripherally inserted central catheter in a patient with spastic hemiplegia after stroke (1例痉挛性偏瘫患者PICC导管部分血栓性堵塞的护理) - SHAN Chenxi (单晨曦); WANG Liangmin (王梁敏); PAN Mengxue (潘梦雪); ZHAO Dandan (赵丹丹) (Association of Integrative Nursing, 2021)
This paper summarized the nursing experience of partial thrombotic blockage of peripherally inserted central catheter (PICC) in a patient with spastic hemiplegia after stroke. Due to the higher nervous system dysfunction after stroke and the long-term flexor state of upper limbs, the patient was vulnerable to catheter-related complications, which increasing the difficulty in catheter maintenance. The partial thrombotic blockage had occurred at two months after PICC placement. After drugs medication and other treatments, PICC was finally safely retained. (本文回顾1例痉挛性偏瘫患者经外周静脉置入中心静脉导管(PICC)部分血栓性堵塞的护理措施。患者中风后高级神经中枢的功能被破坏, 上肢长期屈肌状态, 增加了护士导管维护难度。置管2个月后发生导管内部分血栓性堵塞, 在给予药物等处理后, PICC得以安全留置。)